(untitled) (Journal of the Bangladesh Agricultural University, 2011)
Genetic diversity is essential to meet the diversified goals of plant breeding such as producing cultivars with increased yield, wider adaptation, desirable quality, pest and disease resistance. In this study genetic diversity and selection index of 24 genotypes of bread wheat were evaluated. The performance of 24 wheat genotypes showed that there were significant variations for the characters suggesting the presence of genetic variability among the genotypes. The genotypes were grouped into five clusters viz. I, II, III, IV and V based on Mahalanobis’ D2 statistics. Cluster I and II were the largest group containing six genotypes and the rest three clusters contained four, five and three genotypes respectively. The genotyps belonging to the same group had smaller D2- value than between those belonging to different clusters. Study on selection indices through discriminate function showed that Anza ranked as the best followed by the genotypes Rawal, PBW-373 and Kheri and suggests that these highest scoring genotypes might be recommended for farmers’ cultivation for better yield and it would be expected genetic gain upto 49.77% through selection practices based on the characters studied. Therefore, a crossing programme could be made among the genotypes belonging in cluster I and cluster V will provide maximum heterotic combination, especially for yield of bread wheat. Alternatively, among the studied genotypes Anza could be cultivated for better performance. Keywords: Genetic divergence; Genetic gain; Selection indices; Bread wheat DOI: http://dx.doi.org/10.3329/jbau.v9i1.8736 JBAU 2011; 9(1): 1-4